Cardiovascular pharmacodynamics of donepezil hydrochloride on the PR and QT intervals in patients with dementia. (11th March 2014) - Igeta, Hirofumi; Suzuki, Yutaro; Tajiri, Misuzu; Someya, Toshiyuki
<x xml:space="preserve">Abstract</x> Objective Although several case reports suggested that donepezil hydrochloride can induce bradycardia or atrioventricular block, the details remain unclear. We implemented a study of the impact of donepezil hydrochloride administration on PR, RR, and QT intervals. Methods The subjects were 18 patients who were diagnosed with either dementia or cognitive disorder (DSM‐IV‐TR) and were hospitalized between January 2011 and December 2012. After hospitalization, they were treated with donepezil hydrochloride. Clinical parameters and electrocardiograms before and after the administration of donepezil hydrochloride were retrieved from the patients' medical records. Results After the administration of donepezil hydrochloride, the mean PR interval significantly increased from 177.3 ± 30.9 to 186.8 ± 38.4 ms (p < 0.001). And the mean RR interval also significantly increased from 850.3 ± 112.5 to 886.7 ± 136.4 ms (p = 0.014). The mean difference in the PR interval before and after the administration of donepezil hydrochloride was 9.5 ± 17.1 (range = −21.0–44.0) ms. The QT intervals were unaffected by the administration of donepezil hydrochloride. Conclusions Care should be taken when administering donepezil to patients with atrioventricular block, or patients taking other drugs that can prolong the PR interval. Copyright © 2014 John Wiley & Sons, Ltd.